La Odisea desde la Egiptología - Galán, José M. (Gerión. Revista de Historia Antigua, 2001)
The author's aim is to show how the Classical sources, as in this case the Odyssey, can shine even brighter if they are read from a Near Eastern perspective. Cultures, artists and craftsmen are not isolated phenomena in time and space, and for that matter it is sound to approach the Classic culture and authors from previous times and from near by places with which they themselves or their predecessors maintained contacts. In this paper the author brings together some topics from the Odyssey and their counterparts in ancient Egyptian sources.